Construção do mapa genético preliminar do peixe Prochilodus argenteus, utilizando marcadores microssatélites - Bianchi, Beatriz Cutilak (2009)
A preliminary genetic linkage map was constructed for the species Prochilodus argenteus, an endemic fish from the São Francisco river basin, using 23 microsatellite markers in a progeny with 95 individuals from a single cross by the pseudo-testcross strategy. The male and female parents were collected in different regions, downstream of the dam of the Três Marias (MG). Only 11 (52.4%) markers grouped in some linkage group and the the remaining was unlinked. Twenty-one (91.5%) markers appeared to segregate according to Mendelian inheritance, and only two (8.7%) showed segregation distortion. The map covered 297.58 cM of the genome, according to the Kosambi s function. The number of linkage groups (3) found in this study was much lower than expected for the species (equivalent to the haploid number of chromosomes, n = 27), demonstrating the importance of using a larger number of molecular markers in future studies. The data obtained in this work will be compiled with the marks obtained by AFLP by Rojas (2008) in order to obtain a denser genetic map. Although the number of linkage groups found have been lower than expected for the species, the results can be considered promising for the Brazillian Fish Genetics, since genetic mapping studies are virtually absent in Neotropical fish.